If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(3y + -6) + 4(5y + -8) = 8 Reorder the terms: -1(-6 + 3y) + 4(5y + -8) = 8 (-6 * -1 + 3y * -1) + 4(5y + -8) = 8 (6 + -3y) + 4(5y + -8) = 8 Reorder the terms: 6 + -3y + 4(-8 + 5y) = 8 6 + -3y + (-8 * 4 + 5y * 4) = 8 6 + -3y + (-32 + 20y) = 8 Reorder the terms: 6 + -32 + -3y + 20y = 8 Combine like terms: 6 + -32 = -26 -26 + -3y + 20y = 8 Combine like terms: -3y + 20y = 17y -26 + 17y = 8 Solving -26 + 17y = 8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + 17y = 8 + 26 Combine like terms: -26 + 26 = 0 0 + 17y = 8 + 26 17y = 8 + 26 Combine like terms: 8 + 26 = 34 17y = 34 Divide each side by '17'. y = 2 Simplifying y = 2
| -13y+7+9=-10y-11 | | 9(x+3)-5x-3(5+3x)= | | 0.5n-18=-4 | | -q+17=-2q | | 17c-9=18c-19 | | c/8=41 | | -7+3=-5b+17 | | 2(3x-5x)=4x+12 | | 12n+15=11n | | -16+9-15g=1-11g | | -10+9m+3=m+9 | | 6p=15+7p | | r+3/5=4 | | -3w-8=-9w+10 | | -10-2q=-2-3q | | 10h=-8+2h | | 4+8u=-10+10u | | 6x-27=3 | | 3x-12y=-36 | | -2d+2d+8=-4+2d | | Nsquared-10n+22=-2 | | 5t-5=7+8t | | X^2+5-4x=0 | | 52=f-18 | | 24.4=12.4 | | -3(3x-2)=2x+3 | | 7u=-10+8u | | 6+y=-8+3y | | 4z=3x+3 | | 8+3t+9t=10t-8 | | 6x-5=.2x-.8 | | -20n=40 |